MANAJEMEN PEMASARAN PARIWISATA DALAM MENINGKATKAN KUNJUNGAN WISATAWAN KE KEPULAUAN SERIBU: SEBUAH LITERATUR REVIEW - Irfan Arif Husen (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Tourism is one of the leading sectors in Indonesia’s economic development, including in the Thousand Islands (Kepulauan Seribu), which possesses remarkable marine and natural potential. However, the management and marketing strategies of tourism in this region still face several challenges, such as limited infrastructure, low service quality, and the suboptimal use of digital promotion. This study aims to examine tourism marketing management strategies in the Thousand Islands using a literature review method, in order to provide a comprehensive overview of effective strategies for increasing tourist visits. The literature review was conducted by analyzing various relevant previous studies related to tourism destination management, the concept of the marketing mix (7P), and sustainable tourism approaches. The findings indicate that the application of digital-based marketing strategies, the improvement of tourism service quality, the strengthening of stakeholder collaboration, and the development of a sustainable and environmentally friendly destination image are crucial factors in enhancing the attractiveness of the Thousand Islands. Furthermore, promotional strategies through social media, the enhancement of local human resource capacity, and the development of thematic tourism packages have been proven effective in increasing both tourist arrivals and satisfaction. This study emphasizes the importance of integrated and sustainability-oriented marketing management in the development of tourism in the Thousand Islands. By optimizing natural potential, local culture, and digital technology, the region has the opportunity to become one of Indonesia’s leading tourism destinations. The implications of this review are expected to serve as valuable input for local governments, tourism businesses, and local communities in formulating more effective, sustainable, and competitive marketing strategies both nationally and internationally.